The CKD‐DETECT study: An RCT aimed at improving intention to initiate a kidney health check in Australian practice nurses. Issue 15 (13th May 2019) - Sinclair, Peter M.; Kable, Ashly; Levett‐Jones, Tracy; Holder, Carl; Oldmeadow, Christopher J.
Abstract: Background: The burden of Chronic Kidney Disease (CKD) on the Australian health system is growing. Efforts to reverse this trend have not been successful. This paper evaluates the effectiveness of a targeted asynchronous web based e‐learning module on general practice nurses' behavioural intentions in relation to opportunistic screening practices for people at risk of CKD. Design: Double blinded pre‐post interventional randomised control design. Methods: Participants were nurses working in general practice settings in Australia. Participants were randomised to a knowledge based active control or targeted behavioural based intervention which were delivered using asynchronous e‐learning modules. The intervention was designed to influence the behavioural constructs of the theory of planned behaviour (TPB): attitude, subjective norm and perceived behavioural control (PBC). Results: Of the 420 participants, we analysed the primary and secondary outcomes for 212 (50.47%) who had complete follow up data. There were no significant differences (p 0.424, [d] 0.04) in behavioural intention between the intervention and control groups at follow‐up, when controlling for baseline values. However, regression models assessing the relationship between the change in the TPB constructs and behavioural intention at follow‐up for all participants, regardless of study arm, demonstrated a significant change in intention to initiate a kidney health check. Although these changes could not be attributed to the effect of the intervention. Attitude (r2 = 0.3525, p 0.0004) and PBC (r2 = 0.3510, p 0.0005) models accounted for approximately 35% of the explained variance in behavioural intentions and social norm (r2 = 0.3297, p 0.0171) accounted for approximately 33% of the variance. When all TPB constructs were included in the model, 37% of the variance in intention was explained. Conclusion: A targeted behavioural online intervention was no more effective than a knowledge based online program to improve primary health care nurses' intention to initiate a kidney health check in people at risk of chronic kidney disease. Relevance to clinical practice: Collaborative efforts are required by all staff working in general practice to develop models of care to improve screening practices for chronic kidney disease. Future research should focus on interventions that improve collaboration between health care professionals in the primary care setting and public health campaigns to increase awareness of risks of CKD and the importance of screening in the primary care setting.